Kebijakan Kepala Sekolah dalam Meningkatkan Kinerja Guru SMP Negeri di Kecamatan Keluang Kabupaten Musi Banyuasin - Puji Santoso; Bukman Lian; Nila Kesumawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze in depth the principal’s policies in improving teacher performance at public junior high schools (SMP Negeri) in Keluang District, Musi Banyuasin Regency. The principal plays a strategic role as an educational leader who is responsible for directing, guiding, and developing human resources—particularly teachers—so that they can perform professionally in accordance with the demands of the Merdeka Curriculum. This research employs a descriptive qualitative approach, using data collection techniques such as in-depth interviews, direct observation, and document analysis. The research subjects include principals, teachers, and school supervisors. The findings reveal that the principal’s policies to improve teacher performance are implemented through four main strategies. First, enhancing teacher competence through training, workshops, academic supervision, and continuous professional development activities. Second, implementing reward and sanction systems to foster motivation and discipline among teachers. Third, building a collaborative work culture through subject teacher discussions (MGMP), regular meetings, and reflective teaching activities. Fourth, strengthening participatory leadership by involving teachers in school planning and evaluation processes. These policies have proven effective in improving teachers’ sense of responsibility, creativity, and instructional innovation. Thus, the principal’s role as a transformational leader is crucial in creating a conducive work environment and fostering efforts to improve the quality of education at the junior secondary school level.